TOOTH EXTRACTION FROM A PATIENT WITH CAVERNOUS HEMANGIOMA IN MAXILLOFACIAL REGION: CASE REPORT - Onur Dinçer Köse; Cem Tanyel; Taha Emre Köse; Mehmet Ali Erdem; Abdulkadir Burak Çankaya (Istanbul University, 2016)
Hemangiomas are benign vascular tumors which represent a rapid growth pattern followed by the involution phase. Generally, they are located in the soft tissues and are usually diagnosed in the first decade of life. Hemangiomas are mostly asymptomatic and rarely affect jaw bones. Mandible is affected more often than maxilla. If there is no complication present, treatment may not be necessary. Treatment planning of hemangiomas should be done by considering the location and the size of the lesion as well as the proximity to vital anatomical structures. The aim of this case report is to describe the procedures of tooth extraction in a patient who had been diagnosed as having maxillary cavernous hemangioma.